Right to Information : Identifying Drivers of Effectiveness in Implementation - Trapnell, Stephanie E.; Lemieux, Victoria L. (World Bank, Washington, DC, 2015)
The findings from the study suggest that international pressure for more effective Right to Information (RTI) implementation only goes so far. The development of RTI laws with the encouragement, assistance, or insistence of the international community was a prominent theme throughout the case studies, particularly for EU countries during their accession process. But implementation is a less straightforward task, with many interlocking, moving parts, and international support comes in ad hoc fashion as the process unfolds. A strong implication from these findings is that a national coordinating strategy may be valuable for implementation. This kind of strategy document should take the interdependence of the drivers of effectiveness into account when drafting policies and rules for practice, and can serve as a guiding document when deciding on foreign funding priorities.